FEATURES OF THE CALCULATION OF THE USED PLASTICITY RESOURCE DURING COLD FORMING OF GLASS-TYPE PRODUCTS - KYRYTSYA, Inna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The reverse extrusion process is widely used in the production of "Glass" type parts. Due to high technical and economic indicators and great technological possibilities, in recent years, cold plastic deformation has become widely used in machine- and instrument-building plants, in the electrical and radio engineering industry, as well as in other branches of the national economy. However, the possibility of cold plastic deformation by the extrusion method is not yet sufficiently used. The reason is that, traditionally, during the design of metal pressure processing processes, attention is paid to determining the power parameters and ensuring the geometric accuracy of the workpieces. But this does not allow us to assess the ultimate shape change and technological heredity of the finished products and make a quantitative assessment of the damage of the deformed metal.In this work, the process of forming products of the "Glass" type by reverse cold plastic deformation is investigated, in which the used plasticity resource is taken as the most important parameter responsible for the quality of the products.The method of calculation of the used resource of plasticity of "Glass" blanks in the processes of reverse cold plastic forming is clarified.When calculating the used plasticity resource, the effect of the volume of the stress state scheme is taken into account by using the limit deformation surface instead of the plasticity diagrams.The graphs of distribution of the resource of plasticity by the radius of the workpiece are obtained. From the analysis of the results it follows that the greatest intensity of accumulation of damage occurs in the areas of maximum irregularity of plastic deformation. Points of contact of the punch with the workpiece turned out to be dangerous.The use of hydrostatic support in reverse extraction allowed not only to reduce the degree of plasticity used, but also to obtain a more uniform distribution of it, therefore, to improve the quality of the obtained blanks when reverse extrusion and improve the technological heredity of the finished products.The results obtained in the work can be used to estimate the limit change in shape in similar technological processes, which are accompanied by a volumetric scheme of the stressed state.
Keywords: used plasticity resource; limit deformation; reverse extrusion; cold plastic deformation